Molecular Diagnosis of Chagas Disease in Colombia: Parasitic Loads and Discrete Typing Units in Patients from Acute and Chronic Phases. - Carolina Hernández; Zulma Cucunubá; Carolina Flórez; Mario Olivera; Carlos Valencia; Pilar Zambrano; Cielo León; Juan David Ramírez (Public Library of Science (PLoS), 2016)
BACKGROUND:The diagnosis of Chagas disease is complex due to the dynamics of parasitemia in the clinical phases of the disease. The molecular tests have been considered promissory because they detect the parasite in all clinical phases. Trypanosoma cruzi presents significant genetic variability and is classified into six Discrete Typing Units TcI-TcVI (DTUs) with the emergence of foreseen genotypes within TcI as TcIDom and TcI Sylvatic. The objective of this study was to determine the operating characteristics of molecular tests (conventional and Real Time PCR) for the detection of T. cruzi DNA, parasitic loads and DTUs in a large cohort of Colombian patients from acute and chronic phases. METHODOLOGY/PRINCIPAL FINDINGS:Samples were obtained from 708 patients in all clinical phases. Standard diagnosis (direct and serological tests) and molecular tests (conventional PCR and quantitative PCR) targeting the nuclear satellite DNA region. The genotyping was performed by PCR using the intergenic region of the mini-exon gene, the 24Sa, 18S and A10 regions. The operating capabilities showed that performance of qPCR was higher compared to cPCR. Likewise, the performance of qPCR was significantly higher in acute phase compared with chronic phase. The median parasitic loads detected were 4.69 and 1.33 parasite equivalents/mL for acute and chronic phases. The main DTU identified was TcI (74.2%). TcIDom genotype was significantly more frequent in chronic phase compared to acute phase (82.1% vs 16.6%). The median parasitic load for TcIDom was significantly higher compared with TcI Sylvatic in chronic phase (2.58 vs.0.75 parasite equivalents/ml). CONCLUSIONS/SIGNIFICANCE:The molecular tests are a precise tool to complement the standard diagnosis of Chagas disease, specifically in acute phase showing high discriminative power. However, it is necessary to improve the sensitivity of molecular tests in chronic phase. The frequency and parasitemia of TcIDom genotype in chronic patients highlight its possible relationship to the chronicity of the disease.